Development of Physical Test Brake Speaker Speed Data Model Application in (PPLPD) (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
This study aims to produce a product in the form of software for physical test data processing based on Visual Basic 6.0 to help trainers and athletes to process data from physical tests. This study uses the R & D method (research and development). The results of this study indicate that practicality in the use of application products is really good, practical, and efficient. The findings obtained from this study are in the form of an athlete’s physical test data processing application that makes it easier for the trainer to process the results of physical test data performed by the athlete, this application uses Microsoft visual basic 6.0 programming. The implications of the results of this study are to assist trainers in processing data from the physical tests conducted by the trainers to their athletes, so that the trainers can be helped in processing data in a practical and efficient manne.